A cross sectional study of Mexican caregiver social status, dental knowledge, self‐efficacy, and caregiver/child oral health. A structural equation model. (4th March 2020) - Jolanta, Aleksejūnienė; María del Carmen, Villanueva‐Vilchis; Mónica, Anaya‐Morales
Abstract : Objectives: To test hypothetical models relating caregivers' social status, knowledge, and self‐efficacy to caregiver/child (C/C) oral health‐related outcomes. Methods: One hundred fifty C/C pairs participated (recruitment = 87.7 percent). Three C/C outcomes were clinically assessed: "Oral self‐care"; "Functional dentitions"; and "Dental treatment needs." Information about caregiver (CG) social status, knowledge, and self‐efficacy was also gathered. Structural equation modeling tested measurement models (MMs) for CG social status, CG knowledge, and CG self‐efficacy. The structural models (SMs) hypothesized causal paths among CG social status, CG knowledge, CG self‐efficacy, and C/C oral health outcomes. Results: All three MMs had a good overall fit (nonsignificant χ 2 estimates, Goodness of Fit Index >0.95, Normed Fit Index >0.95, Confirmatory Fit Index >95, Root Mean Square Error Approximation <0.05). For the SMs, the best overall fit was for "Functional dentitions, " while SMs for "Oral self‐care, " and "Dental treatment needs" required revisions. In all the SMs, the path between "Caregiver social status" and "Caregiver knowledge" was significant. In the "C/C Functional dentitions" SM, the significant path linked "CG self‐efficacy" and "Child functional dentition." In the "C/C Dental treatment needs" SM, the significant path linked "CG self‐efficacy" and "CG functional dentition." Conclusions: Hypothetical models for three oral health‐related outcomes were partly or fully validated.